Progress towards health systems strengthening in Myanmar - Susan Becker (Inishmore Laser Scientific Publishing Ltd, 2018)
# Objectives This is a commentary on the health care system of Myanmar during the ongoing transition to a new "democratic" government intent on engaging with the international community. In the years Myanmar was isolated, its health system remained undeveloped and underfunded with large disparities in health outcomes for poor, indigenous populations. # Study design Observational, descriptive. # Methods Observations, published reports, data, conferences, and interviews. # Results Decades of under-investment have resulted in critical shortages of human resources for health. Although improvements are slowly being made by government, poor, indigenous people have developed a system of community health workers and auxiliary midwives to meet the needs of their communities. The government plans to develop a national emergency ambulance system but there are systemic factors that delay progress towards modernization and equity in health care. # Conclusions Health care decision-makers remain constrained by the legacy of strict hierarchical structures, limited decision-making capacity and political uncertainty. Structural and cultural factors delay progress in health system strengthening and equity in poor, indigenous regions. In Myanmar change is a slow and complicated process with many obstacles to overcome.